Inhibition of local aldosterone by eplerenone reduces renal structural damage in a novel model of chronic cyclosporine A nephrotoxicity. (June 2015) - Sun, Qiao-Ling; Li, Meng; Rui, Hong-Liang; Chen, Yi-Pu
Background and objective: The fact that mineralocorticoid receptor antagonists reduce structural and functional alterations induced by cyclosporine A (CsA) indicates that aldosterone plays a key role in chronic CsA nephrotoxicity. We and other researchers have reported local renal aldosterone synthesis. To investigate local renal aldosterone's role in chronic CsA nephrotoxicity, we evaluated the effect of eplerenone (Epl) on renal structural damage and renal dysfunction in adrenalectomized (ADX) rats, and assessed whether the therapeutic benefit was associated with reduction of transforming growth factor-β1 (TGF-β1), connective tissue growth factor (CTGF), plasminogen activator inhibitor type 1 (PAI-1) and collagen I (COL-I) expression. Methods: Male Sprague-Dawley rats fed a normal-sodium diet were divided in four groups: sham-ADX, ADX, CsA, or Epl. Rats in the ADX, CsA and Epl groups were adrenalectomized first. Aldosterone, sodium and potassium levels in serum and urine were measured on the second day. Two weeks later, vehicle (sham-ADX and ADX group), CsA (25mg/kg/d), or CsA and Epl (100 mg/ kg/d) combination was administrated, respectively. After six weeks, urinary protein, creatinine clearance (Ccr ), tubulointerstitial fibrosis (TIF), aldosterone level in kidney, and renal aldosterone synthase CYP11B2, COL-I, TGF-β1, CTGF and PAI-1 gene expression levels were determined. Results: On the second day after surgery, adrenalectomized rats showed undetectable aldosterone with natriuresis, hyponatremia, decreased urinary potassium excretion and hyperpotassemia. CsA reduced Ccr, induced urinary proteins and up-regulated COL-I, TGF-β1, CTGF and PAI-1 gene expression with a significant development of TIF. Eplerenone administration prevented TIF and COL-I, TGF-β1 and PAI-1 up-regulation but did not improve renal function. Conclusion: Our results suggest local renal aldosterone is an important mediator of renal injury induced by CsA.